2018
DOI: 10.1007/s00299-017-2247-4
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study of cold tolerance of Chinese indica rice varieties at the bud burst stage

Abstract: Key message A region containing three genes on chromosome 1 of indica rice was associated with cold tolerance at the bud burst stage; these results may be useful for breeding cold-tolerant lines. Abstract Low temperature at the bud burst stage is one of the major abiotic stresses limiting rice growth, especially in regions where rice seeds are sown directly. In this study, we investigated cold tolerance of rice at the bud burst stage and conducted a genome-wide association study (GWAS) based on the 5K rice arr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 45 publications
(60 reference statements)
1
29
0
Order By: Relevance
“…Further, two major M-QTLs, qLTG(I) 1 (16.08%) and qLTGS(I-II) 1 (16.57%), on chromosome 1 at the 41.0 to 42.4 Mb region were clearly associated with the germination and seedling tolerance QTLs qCTGERM1-8 and qCTS1-5 and the other QTLs qSW1-1 to qSW1-4 (seed weight per plant) and qSWTCT1-1 (seed weight per panicle) expressed in the same genomic region under cold stress at the reproductive stage (Cui et al 2013;Yang et al 2016;Shakiba et al 2017). Similarly, two other QTLs, qLTG(I) 5 (18.56%) and qLTGS(I) 5 (23.38%), on chromosome 5 at the 28.65 Mb region were concomitant with qSWTNCT5 (seed weight per panicle), qCTB5 (cold tolerance at booting stage), and seedling-stage QTLs qCTSR5-1 (cold tolerance seed survival rate) and qCTSD5-2 (cold tolerance severity of damage) (Andaya and Mackill 2003b;Ranawake et al 2014;Shakiba et al 2017;Zhang et al 2018b). Lastly, qLTG(I) 7 (20.12%) located on chromosome 7 at 3.85 Mb is a novel locus, which is co-localized with second germination stage QTL LTG(II) (8.25%).…”
Section: Prime M-qtls For Future Breeding Programsmentioning
confidence: 88%
See 1 more Smart Citation
“…Further, two major M-QTLs, qLTG(I) 1 (16.08%) and qLTGS(I-II) 1 (16.57%), on chromosome 1 at the 41.0 to 42.4 Mb region were clearly associated with the germination and seedling tolerance QTLs qCTGERM1-8 and qCTS1-5 and the other QTLs qSW1-1 to qSW1-4 (seed weight per plant) and qSWTCT1-1 (seed weight per panicle) expressed in the same genomic region under cold stress at the reproductive stage (Cui et al 2013;Yang et al 2016;Shakiba et al 2017). Similarly, two other QTLs, qLTG(I) 5 (18.56%) and qLTGS(I) 5 (23.38%), on chromosome 5 at the 28.65 Mb region were concomitant with qSWTNCT5 (seed weight per panicle), qCTB5 (cold tolerance at booting stage), and seedling-stage QTLs qCTSR5-1 (cold tolerance seed survival rate) and qCTSD5-2 (cold tolerance severity of damage) (Andaya and Mackill 2003b;Ranawake et al 2014;Shakiba et al 2017;Zhang et al 2018b). Lastly, qLTG(I) 7 (20.12%) located on chromosome 7 at 3.85 Mb is a novel locus, which is co-localized with second germination stage QTL LTG(II) (8.25%).…”
Section: Prime M-qtls For Future Breeding Programsmentioning
confidence: 88%
“…Through genome-wide association studies (GWAS) approaches, 97 QTLs were identified for LTS tolerance at the germination stage (Pan et al 2015;Sales et al 2017;Schläppi et al 2017). In a similar way, 211 QTLs for seedling-stage tolerance and 72 QTLs for booting-stage tolerance were identified while using diverse rice genetic resources (Pan et al 2015;Lv et al 2016;Wang et al 2016a;Shakiba et al 2017;Xiao et al 2018;Zhang et al 2018b).…”
Section: Introductionmentioning
confidence: 99%
“…GWAS is an e cient way to analyze genetic variation for multiple traits in rice (Lu et al 2016;Zhang et al 2018). In GWAS, accuracy and precision are in uenced by population structure, kinship, and LD decay rate.…”
Section: Gwas Results Analysis Among Different Association Panelsmentioning
confidence: 99%
“…Indica varieties are widely grown in double-rice cropping regions in subtropical zones, and is frequently harmed by exposure to low temperatures at the germination stage. Due to the lower cold tolerance than japonica, the studies of modern indica cultivated rices for cold tolerance are limited [24]. In our study, two double-cropped indica rice varieties CHT025 and WFB were used to address the genetic basis of cold tolerance for the first time.…”
Section: Genetic Basis For Indica Cold Tolerancementioning
confidence: 99%
“…It is noticeable that most QTLs for cold tolerance detected by the populations deriving from crosses between indica and japonica cultivars, such as Nipponbare/9311 [19] and 02428/CH891 [6], because indica rice varieties are more sensitive to low temperatures, and suffer cold stress more frequently, than do varieties of the japonica subspecies [20][21][22]. Although japonica rice is generally more cold tolerant than indica rice, there might be favorable alleles for cold tolerance existing in indica that can be used to enhance cold tolerance [23,24]. However, less analyses were carried out to detect the QTLs associated with cold tolerance using indica/indica population, especially for the double-cropped indica varieties.…”
mentioning
confidence: 99%